2021
DOI: 10.3390/ijms22189894
|View full text |Cite
|
Sign up to set email alerts
|

A Novel L-Asparaginase from Hyperthermophilic Archaeon Thermococcus sibiricus: Heterologous Expression and Characterization for Biotechnology Application

Abstract: L-asparaginase (L-ASNase) is a vital enzyme with a broad range of applications in medicine and food industry. Drawbacks of current commercial L-ASNases stimulate the search for better-producing sources of the enzyme, and extremophiles are especially attractive in this view. In this study, a novel L-asparaginase originating from the hyperthermophilic archaeon Thermococcus sibiricus (TsA) was expressed in Escherichia coli, purified and characterized. The enzyme is optimally active at 90 °C and pH 9.0 with a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…1,2 This enzyme displays great potential for a wide range of applications in the food and pharmaceutical industries, such as reducing the formation of carcinogenic acrylamide in fried foods and treating acute lymphoblastic leukemia (ALL). 3 Due to the short half-life, commercial L-ASNase coming from Escherichia coli (EcA) and Erwinia chrysanthemi (ErA) have a high-dose-dependent disadvantage for ALL treatment, 4 causing severe toxic effects on patients. 5 In addition, the low thermal stability of L-ASNase hinders acrylamide mitigation efficiency in thermally processed food, 6,7 which also increases the risk of microbial contamination and overall production costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This enzyme displays great potential for a wide range of applications in the food and pharmaceutical industries, such as reducing the formation of carcinogenic acrylamide in fried foods and treating acute lymphoblastic leukemia (ALL). 3 Due to the short half-life, commercial L-ASNase coming from Escherichia coli (EcA) and Erwinia chrysanthemi (ErA) have a high-dose-dependent disadvantage for ALL treatment, 4 causing severe toxic effects on patients. 5 In addition, the low thermal stability of L-ASNase hinders acrylamide mitigation efficiency in thermally processed food, 6,7 which also increases the risk of microbial contamination and overall production costs.…”
Section: Introductionmentioning
confidence: 99%
“…l -Asparaginase ( l -ASNase, amidohydrolase enzyme, EC3.5.1.1) can catalyze the production of non-essential amino acid l -asparagine (L-ASN) to l -aspartic acid (L-ASP) and ammonia. , This enzyme displays great potential for a wide range of applications in the food and pharmaceutical industries, such as reducing the formation of carcinogenic acrylamide in fried foods and treating acute lymphoblastic leukemia (ALL) . Due to the short half-life, commercial l -ASNase coming from Escherichia coli (EcA) and Erwinia chrysanthemi (ErA) have a high-dose-dependent disadvantage for ALL treatment, causing severe toxic effects on patients .…”
Section: Introductionmentioning
confidence: 99%
“…It appears that adaptation at high environmental temperatures involves an increase in K M and k kat for thermophilic L-ASNases [53]. This characteristic feature allows optimiz-ing catalytic efficiency by reaching a balance between substrate binding and the rate of product release.…”
Section: Discussionmentioning
confidence: 99%
“…The same doubt was expressed about the type I enzyme of archaea from Pyrococcus horikoshi , which acts as a dimer rather than a tetramer [ 33 ]. L-ASNases of some extremophile bacterial organisms [ 61 ], for example, Thermus thermophilus [ 62 ], Thermococus sibiricus [ 63 ] or Melioribacter roseus [ 64 ], can act as hexamers (trimers of dimers), but there is no structural evidence to support this hypothesis. It is believed that the dimer of L-ASNase II, which has two active centers, is not able to cleave L-asparagine.…”
Section: Structures Of L-asnases and The Mechanism Of Actionmentioning
confidence: 99%
“…Zuo et al [ 152 ] reported the cloning and expression of a new thermostable L-ASNase from Thermococcus zilligii that showed maximum activity at pH 8.5 and a temperature of 90 °C, the highest ever observed. A later L-ASNase from Thermococus sibiricus demonstrated similar thermal stability and was 86% active after 20 min of incubation at 90 °C [ 63 ].…”
Section: Alternative Approaches To the Development Of Antitumor L-asn...mentioning
confidence: 99%